(untitled) (Research, Society and Development, 2021)
To analyze the understanding of Primary Health Care workers about the health and aging condition of people with Down Syndrome. Qualitative-quantitative, exploratory approach, carried out with Primary Health Care workers in a municipality in southern Brazil. The data were collected through interviews, analyzing the Collective Subject Discourse for qualitative and quantitative data, which were treated descriptively. 57 workers participated. There was a predominance of females (82.5%). The general average age, regardless of gender, was 44.8 years. From the analysis of the Collective Subject Discourse, four themes emerged: i) workers’ conceptions about people with Down Syndrome; ii) the perception of workers about the health of people with Down Syndrome; iii) comprehensive care for people with Down Syndrome and iv) (re) knowledge of the Multidimensional Rapid Assessment of the Elderly and the prospecting of health care for people with Down Syndrome. It was found that the care of people with Down Syndrome is still strongly linked to specialized services, that is, the relationship between these people and Primary Health Care is fragile, it is linked beyond their physical, cognitive and behavioral differences people.